A Comparison of Domestic Violence Settlement from the Perspective of Islamic Law and Positive Law in Indonesia - Yani Andriyani; Hamzah Fansuri; Hamzah Fansuri (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
The numerous cases of household violence in Indonesia suggest that the state still has significant work to do in addressing it. Despite having its claim laws, it appears that their execution still has deficiencies. The purpose of this paper is to examine how Islamic Law and Positive Law in Indonesia compare to Domestic Violence. A qualitative method with a normative approach is employed in this research. The research results show that the sanctions prescribed in Islamic law are based on the application of takzir, qishash, and diat. Meanwhile, positive law provides criminal sanctions and fines. The primary objective in criminal acts of physical violence within the family is to deter or punish the perpetrator so that peace and the progression of community life are maintained. The state plays a role in enforcing amar ma'ruf nahi munkar, including in household matters. The state is obliged to provide protection, services, and recovery for victims.